Preterm birth and periodontal disease: A medical perspective - Neeta Dhabhai (Wolters Kluwer Medknow Publications, 2016)
Births occurring before 37 weeks resulting in prematurity poses serious hazards to the baby from delayed growth, neurodevelopmental anomalies to death and unfortunately India is in the top four countries with maximum preterm births and leads globally in deaths by prematurity. Infection is a very important component of the etiopathogenesis of preterm labor and periodontal disease is a rather unexplored aspect of infection very often overlooked by the general gynecologist and the dental practitioner equally. Periodontal disease is a potential foci of infectious pathogens which may disseminate hematogenously and effect the fetus. In this article, an effort has been made to find an evidence-based link between periodontal disease and preterm labor to drive home the conclusion that an early screening and diagnosis in pregnancy followed up with effective treatment of periodontal disease may significantly reduce the burden of preterm births.